2020
DOI: 10.1063/5.0012594
|View full text |Cite
|
Sign up to set email alerts
|

Defect, transport, and dopant properties of andradite garnet Ca3Fe2Si3O12

Abstract: There is growing interest to discover suitable calcium containing oxides that can be used as electrode materials in calcium ion batteries. A comprehensive computational investigation of ionic defects and Ca-ion diffusion in Ca-bearing oxide materials at the atomic level is important so as to predict their suitability for use in Ca-ion batteries. In this study, we apply atomistic simulation techniques to examine the energetics of defects, dopants, and Ca-ion diffusion in Ca3Fe2Si3O12. The calculations suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Atomistic simulations based on the classical pair potentials can provide useful information on diffusion pathways and activation energies as this information is generally difficult from the experiment. The present methodology has been successfully applied to various ionic materials to calculate migration pathways together with activation energies [11,12,25,26]. For example, there is an excellent agreement between calculated and experimentally determined Li-ion diffusion pathway in LiFePO 4 [43,44].…”
Section: Calcium Ion Diffusionmentioning
confidence: 68%
See 1 more Smart Citation
“…Atomistic simulations based on the classical pair potentials can provide useful information on diffusion pathways and activation energies as this information is generally difficult from the experiment. The present methodology has been successfully applied to various ionic materials to calculate migration pathways together with activation energies [11,12,25,26]. For example, there is an excellent agreement between calculated and experimentally determined Li-ion diffusion pathway in LiFePO 4 [43,44].…”
Section: Calcium Ion Diffusionmentioning
confidence: 68%
“…Furthermore, calcium-bearing minerals are of interest in the development of electrode materials for rechargeable Ca-ion batteries [9]. Though CaAl 2 Si 2 O 8 was not studied for this purpose yet, theoretical investigation on other Ca-based minerals is available [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In general, Ca ion diffusion in Ca-bearing oxide materials is expected to be sluggish due to its ions with double positive charge. In previous theoretical simulations based on the DFT and classical pair potentials, it was shown that activation energies of Ca ion diffusion in Ca-based minerals are high, confirming the slow diffusion [49][50][51][52].…”
Section: Calcium Ion Diffusionmentioning
confidence: 76%
“…Magnesium and calcium are interesting alternative ions to Li, which have the advantage of being divalent [17,45,[106][107][108][109][110][111][112][113][114][115][116][117][118][119]. Here we will consider Mg as a potential divalent ion to substitute Li as the diffusion of Ca ions in crystal lattices is plagued by its larger ionic radius.…”
Section: Magnesium-ion Batteriesmentioning
confidence: 99%